Design for microassembly: a methodology for product design and process selection - Tietje, Carsten (2009)
The thesis presents research carried out in the field of design for microassembly (DFµA), a field that has hereto been characterised by the absence of well defined methodologies intended to facilitate transfer of prototypes from the research lab to production on industrial scale. A DFμA methodology has been developed, serving the purpose of integrating product and micro assembly process development. It aims in particular at increasing the efficiency of the microproduct development process, decreasing the development time and the product and process cost, and enhancing the product quality. Chapter 1 presents the motivations, objectives, and structure of the thesis. The work carried out is inspired by the need to overcome barriers currently existing between the making of single research products and production on an industrial level. The main objective is to contribute to the creating of a novel DFμA that supports product design and process selection, thereby facilitating the efficient assembly of complex three-dimensional miniaturised devices. This is complemented by a range of secondary targets that deal with the development and verification of supporting methods and models related to DFμA. The summary of a comprehensive literature review is given in chapter 2. The survey provides results of studies closely related to the work reported in this thesis and relates that work to a larger ongoing dialogue about the topic of assembly and design in the microworld. Chapter 3 outlines the research approach adopted here for the developing of a DFμA methodology. It carefully analyses the way in which the knowledge gaps identified can be addressed and how the stated objectives can best be achieved. The key contributions made to the developing of a DFμA methodology are presented in chapters 4,5, and 6. The micro assembly process capability model is described first, in Chapter 4. It constitutes the first attempt made at introducing a general framework for capturing of microassembly characteristics. The model developed enables selection and characterisation of microassembly processes. A framework to characterise the model's application to microjoining, -feeding, and -handling is as well suggested. Chapter 5 concerns the actual DFμA methodology. The methodology's layout and structure are introduced in detail. Moreover, the main functions and key phases of the methodology are explained. Special attention is paid to the integration of the microassembly process capability model and to the development of further elements used within the methodology, such as support in product design. Provided in Chapter 6 is a comprehensive analysis of conventional DFA guidelines, intended to explain how the microspecific guidelines have been formulated. The chapter also describes how these are implemented within the overall DFμA methodology. The procedure of validating and illustrating the methodology, which includes applying it to practical test cases, takes place in Chapter 7. The thesis is concluded in Chapter 8, wherein evidence of the originality of the knowledge contribution achieved through the work presented is highlighted. Opportunities for further research work building on the